Analytical Solution of Scattering by a 2D Dielectric Filled Crack in a Ground Plane Coated by a Dielectric Layer: TM Case - Ghalamkari, B.; Tavakoli, A; Dehmollaian, M. (Applied Computational Electromagnetics Society Journal (ACES), 2021)
In this paper, KP method is applied to study the scattering of a 2D loaded crack on a ground plane, coated by a dielectric layer for TM case. For simplicity, the geometry is divided into three regions, whose fields are expressed in terms of Bessel eigen functions. The governing equations involve several infinite summations with infinite number of unknown coefficients. By the use of Weber-Schafheitlin discontinuous integrals, these infinite summations could efficiently be truncated with high numerical accuracy. Boundary conditions are applied to determine unknown coefficients. We employ finite element method (FEM) and convergence analysis to confirm our results. Finally, the influence of coating dielectric layer and filling material is investigated on the scattered field.